Déplacer au nom de la sauvegarde patrimoniale et du développement économique ? - Marie Bridonneau (L'Espace Politique)
This article analyzes a program implemented to displace 700 households living around Lalibela rock-hewn churches in Ethiopia, registered in the UNESCO World Heritage List since 1978. Actors involved in this project fall within different scales and set up their action in national and global practices of resettlement. All legitimize this displacement by mobilizing two main arguments: heritage conservation and economic development. Existing as a rumor since the 1960s, the resettlement has finally started in 2009 after an agreement between World Bank and Ethiopian government for the development of sustainable tourism in Ethiopia. Then, a brutal and nonlinear implementation has begun, showing up unstable power relationships between dwellers, public and ecclesiastic Ethiopian actors, and international actors. By analyzing discourses and practices of these actors throughout the resettlement planning and the first steps of its implementation, we propose a contemporary assessment of urban restructuring by « creative destruction » in a small Ethiopian town.